TEACHER'S RESPONSIBILITY IN FORMING STUDENTS' COMPETENCIES - Rakhmatullaeva N.A. (Scholar Express Journal, 2023)
This article students competencies in formation of the pedagogue responsibility about written. Industry news, new knowledge, modern approaches are changing day by day. At a time when changes are accelerating in the field of education, students are tasked with forming the necessary knowledge, skills and competencies for their future professional activities during their educational activities
Keywords: Student; competence; form; pedagogue